2006
DOI: 10.1097/01.sla.0000202180.16723.03
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sphincter-Preserving Total Mesorectal Excision With Colonic J-Pouch Reconstruction

Abstract: Laparoscopic TME with colonic J-pouch reconstruction is a safe procedure with reasonable operating time and does not appear to pose any threat to the oncologic and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 41 publications
11
59
0
1
Order By: Relevance
“…16 Similarly, Tsang et al from Hong Kong had only 1 anastomotic leak in their series of 105 laparoscopic rectal cancer resections and Li reported a leak rate of 3.5% in his series of 152 patients. 21,22 Laparoscopic TME has the potential to achieve better preservation of the pelvic autonomic nervous system because the magnified operative view allows easier identification of pelvic nerves. Liang et al studied 98 patients with T3 mid or low rectal cancers undergoing laparoscopic TME following neo-adjuvant chemo-radiotherapy.…”
Section: Potential Benefits Of Laparoscopic Rectal Cancer Surgerymentioning
confidence: 99%
“…16 Similarly, Tsang et al from Hong Kong had only 1 anastomotic leak in their series of 105 laparoscopic rectal cancer resections and Li reported a leak rate of 3.5% in his series of 152 patients. 21,22 Laparoscopic TME has the potential to achieve better preservation of the pelvic autonomic nervous system because the magnified operative view allows easier identification of pelvic nerves. Liang et al studied 98 patients with T3 mid or low rectal cancers undergoing laparoscopic TME following neo-adjuvant chemo-radiotherapy.…”
Section: Potential Benefits Of Laparoscopic Rectal Cancer Surgerymentioning
confidence: 99%
“…Recent studies (14)(15)(16) reported the feasibility of total colectomy or proctocolectomy using a laparoscopic approach. We selected a hand-assisted approach for this case in order to maintain a clean operative field by blocking the dilated colon with the surgeon's hand.…”
Section: Discussionmentioning
confidence: 99%
“…The level of the coloanal anastomosis was a median 3.5 (0-4.5) cm from the anal verge; a coloanal pull-through anastomosis was required in one patient who had a distal cancer. The ileostomies functioned and patients tolerated free fluids at a median of two (1-9) days, and the median postoperative hospital stay was seven (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) days. At a median follow-up of 14 (2-33) months, none of the adenocarcinoma patients who had lmdergone curative resection had recurrences.…”
Section: Methodsmentioning
confidence: 99%